The National Research Foundation : Does it have all What it Desired for? - Chauhan, Vipin (Voices of Teachers and Teacher Educators, 2019)
The draft national education policy 2019 strongly advocates a Research Foundation at the national level (chapter 14, p. 264) to promote research in varied academic disciplines. This idea, not a new one, has however been given due recognition for the first time in this draft policy. The draft has tried to articulate the objectives, functions and operational modalities for visualisation education in a new outlook in great detail. There are however several aspects, which are worthy to include in visualising the Research Foundation holistically. This paper tries to indicate some of the possibilities, which may strengthen the significance of its importance.